MICROPARTICLES OF ORE MINERALS IN THE LUNAR REGOLITH FROM MARE FECUNDIDATIS: (CU, AU, AG)4ZN, AG, AU, SN, PB, SB, RE, MOS2, CDS, AUS, AND RHI3 - Bogatikov O.A.; Mokhov A.V.; Kartashov P.M.; Gorshkov A.I.; Magazina L.O.; Ashikhmina N.A.; Koporulina E.V. (My University, 2004)
The absence of new mineral material from the Moon has caused a loss of interest in the mineralogical problems of the Earth's nearest neighbor. However, the application of new high-precision apparatus for study of the lunar regolith sampled by Soviet automatic stations (AS) Luna-16, Luna-20, and Luna-24 has shown that old material hides a great deal of interesting information. The present paper describes several metals, alloys, and sulfides identified in one sample from the Mare Fecundidatis regolith recovered by the AS Luna-16. All the EDS spectra contain carbon and oxygen peaks presumably related to the fluorescence of organic carbon tape.